2006
DOI: 10.1177/0192513x05286019
|View full text |Cite
|
Sign up to set email alerts
|

Grandchildren's Perceptions of Caring for Grandparents

Abstract: Throughout the life course, all family members can expect to find themselves in some type of caregiving role. Individuals may find themselves providing care for a child or for an older family member who needs assistance. With the increase in life expectancy and the shrinking family size, individuals may find themselves spending time providing care to older family members. Despite the fact that caregiving related issues are well researched in the field of gerontology, the developmental experiences of grandchild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
87
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 70 publications
8
87
0
2
Order By: Relevance
“…These relationships, although not as frequent as other care relationships such as the aging parent-adult child dyad, are becoming more common. For example, in 2000 it was estimated that grandchildren accounted for 8 per cent of caregivers in the United States (Foundation 2003, as cited in Fruhauf et al 2006). Young adults and children sometimes act as an additional source of care to that provided by their parents, and they may find in this activity a way to return to their grandparents the support they received from them earlier in their lives (Fruhauf et al 2006;Szinovacz 2008).…”
Section: Changes In Proportions Of Caregivers Across Birth Cohortsmentioning
confidence: 99%
See 2 more Smart Citations
“…These relationships, although not as frequent as other care relationships such as the aging parent-adult child dyad, are becoming more common. For example, in 2000 it was estimated that grandchildren accounted for 8 per cent of caregivers in the United States (Foundation 2003, as cited in Fruhauf et al 2006). Young adults and children sometimes act as an additional source of care to that provided by their parents, and they may find in this activity a way to return to their grandparents the support they received from them earlier in their lives (Fruhauf et al 2006;Szinovacz 2008).…”
Section: Changes In Proportions Of Caregivers Across Birth Cohortsmentioning
confidence: 99%
“…For example, in 2000 it was estimated that grandchildren accounted for 8 per cent of caregivers in the United States (Foundation 2003, as cited in Fruhauf et al 2006). Young adults and children sometimes act as an additional source of care to that provided by their parents, and they may find in this activity a way to return to their grandparents the support they received from them earlier in their lives (Fruhauf et al 2006;Szinovacz 2008). It is unknown whether the provision of care by grandchildren displaces the assistance provided by other members of the family, or rather adds to the latter, thus increasing the size of the care network of elderly persons.…”
Section: Changes In Proportions Of Caregivers Across Birth Cohortsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies examining the significance of the intergenerational relationship concluded that the relationship continues to be highly valued, personally meaningful, and potentially important (Kemp, 2005). Adult grandchildren may even contribute to their grandparents' well-being by providing emotional and practical support (Fruhauf et al, 2006). For example, adult grandchildren may introduce new technologies and instruct their grandparents in how to operate them.…”
Section: Importance Of the Relationshipmentioning
confidence: 99%
“…Although such support can also be provided by other young people, for instance in the context of intergenerational programs, adult grandchildren are more easily approached because many older people maintain contact with younger generations only within the family context. Furthermore, grandchildren, and in particular adult grandchildren, may assist a grandparent in need of care (e.g., Fruhauf et al, 2006), even though they are generally not the first in order of preferred care providers.…”
Section: Importance Of the Relationshipmentioning
confidence: 99%